Validity of Shunt Pumping Test as a Screening Modality for Shunt Block: An Experimental Study - Sharma, Manish; Kumar, Suman (Indian Journal of Neurosurgery, 2020)
Purpose To ascertain the validity and efficacy of shunt compression test in evaluating a blocked shunt.Methods An experimental model was created using a Chhabra shunt, and 25 physicians with 1 to 3 years of experience in neurosurgery were asked to assess the block in the model where artificial blocks were created.Results The sensitivity of test to detect any block was found to be 0.76 (95% confidence interval [CI]: 0.7–0.81), specificity was 0.71 (0.59–0.81), positive likelihood ratio 2.59 (1.81–3.7), and negative likelihood ratio 0.34 (026–0.45). Odds ratio for proximal block was 4.33 (95% CI: 2.01–8.92), and for distal block, it was 10.63 (95% CI: 10.63–22.32). Furthermore, predictive probability for shunt block was maximum when both the ends were considered to be blocked by the investigator and the test was found to be poor in predicting a patent shunt.Conclusion This is not a very reliable screening test to detect presence of a shunt block. Predicted probability for shunt block was maximum when both the ends were considered to be blocked by the investigator. This study results are not in conformity with the previously held belief that delayed refilling of chamber would clearly aid the diagnosis of proximal end block. It is strongly felt that a deliberate training of shunt compression test would aid a better diagnostic ability.
Keywords: hydrocephalous; manual chamber compression test; ventriculoperitoneal shunt; blocked shunt